Impact of Hajj on the S. pneumoniae carriage among Indian pilgrims during 2016- a longitudinal molecular surveillance study. Issue 23 (May 2018) - Ganaie, Feroze; Nagaraj, Geetha; Govindan, Vandana; Basha, Reyaz; Hussain, Mohib; Ashraf, Nazar; Ahmed, Shafique; Ravi Kumar, K.L.
Abstract: Background: The population flow dynamics of Hajj increases the probability of pneumococcal acquisition and amplification among Hajis. This multi-site longitudinal molecular surveillance study was designed to assess the impact and potential variations of pneumococcal carriage in a single cohort of pre and post-Hajj pilgrims from India. Method: A total of 3228 pre and post-Hajj, nasopharyngeal and oropharyngeal swabs were collected from 807 pilgrims with an interval of 40 ± 5 days. The carriage was detected by culture and qmPCR. Quellung test, mPCR-FAF, PCRseqTyping, and MLST was used for typing. Antibiogram was performed by MIC method. Results: An increased incidence of pneumococcal carriage was detected in post Hajj cohort by qmPCR (19% vs 21.8%) (p-value = 0.0487) and culture (6.5% vs 8.2%) (p-value = 0.0645). Fragment analysis could identify multiple serotype carriage in 76 pilgrims. Increase in drug resistance was also observed in post-hajj cohort for Tetracycline (29% vs 51%), Erythromycin (26% vs 46%) and Levofloxacin (6% vs 17%). Multidrug resistant strains in post Hajj group was 32% compared to 11% in pre Hajj group (p-value = 0.0002). Conclusion: Our results confirm high acquisition rate of multidrug-resistant S. pneumoniae in Hajj pilgrims and highlight its potential spread to home countries upon their return. Surveillance studies are needed to evaluate modifiable factors associated with carriage.